Detection of IHHNV in Litopenaeus vannamei farms in Costa Rica - Parajeles Mora, Jose Francisco; Peña Navarro, Nelson; Solorzano Morales, Anthony; Dolz, Gaby (Agronomía Mesoamericana, 2021)
Introduction. The infectious hypodermal and haematopoietic necrosis virus (IHHNV) produces cuticular deformities and growth reduction of white shrimp (Litopenaeus vannamei) causing losses due to a lower harvest weight and lower market prices. Although different pathogenic and non-pathogenic genotypes of IHHNV have been described, it is unknown whether these are present in the country. Objective. To characterize the IHHNV lineages present in white shrimp farms in Costa Rica. Materials and methods. Between 2017 and 2018, a total of 15 shrimp farms distributed in the Gulf of Nicoya, Guanacaste, Costa Rica were investigated. Water, postlarvae, and juvenile shrimp samples were collected during a production cycle of three months, additionally, physicochemical parameters of the water in the ponds were measured and a survey was applied to the producers, to know if they had knowledge about the disease and if they suspected the presence of the agent in their establishments. The collected samples were analyzed by Polymerase Chain Reaction (PCR) and sequencing. Results. The presence of IHHNV was determined in 86.6 % (13/15) of the farms analyzed, the sequencing of the amplified products determined the presence of IHHNV lineage III, with 99.2 %-100.0 % (386-389/389 bp) similarity with the sequence isolated from L. vannamei in Venezuela (KM485615.1). Poor physicochemical parameters of the water were determined. A total of 53.3 % of producers had not heard of IHHNV, while the remaining producers suspected having the virus on their farms. Conclusion. IHHNV pathogenic lineage III was present in most of the farms. It is recommended to train producers and establish welfare, management, and biosecurity protocols in order to improve the productive parameters of their farms.